Development and Validation of a Website on Early Childhood Nutrition - Esam, Fatin Najiha; Muniandy, Naleena Devi (Jurnal Gizi dan Pangan, 2024)
This study aimed to develop and determine the content and face validation of eHealth website that can function as a one-stop information center for parents, caregivers, teachers, and healthcare professionals on early childhood nutrition. This study was divided into two phases. Phase 1 involved website development and was executed in three steps: Step 1: Need Assessment, Step 2: Design Arrangement, and Step 3: Website Construction. Phase 2 involved website validation, which included content validation by six professionals in nutrition/dietetics and early childhood education fields and face validation by six professionals and 50 target users, including parents, caregivers, nursery or preschool teachers, and students. The content validation obtained a score of 1.00. The face validation by professionals exceeds the minimum value of 80% except for the Quality of Information. In comparison, face validation by the users exceeds 80% except for Subjective Quality. Krippendorff’s Alpha for each validation was below 0.66. In conclusion, the content validation of the website indicated high agreement, while the face validation indicated sufficient by the professionals and target users. The website will be a good start for intervening in long-term nutrition-related issues such as non-communicable diseases and obesity, as eating habits and food choices from young affect future health outcomes.